Особистісно професійне вдосконалення студентів технічного ВНЗ - Попова, Галина Вікторівна (НТУ "ХПІ", 2009)
В статті наводяться данні щодо зацікавленості студентів технічного ВНЗ в самовдосконаленні за допомогою соціально-психологічного тренінга. Наводиться характеристика потреб студентів в самовдосконаленні в особистістному та професійно-особистістному аспектах.

In the article these researches of interest of students of technical institute of higher are presented to personality self-perfection through the socially-psychological training. The necessities of students are characterized in self-perfection in personality and professionally-personality aspects.
Personality-professional sovershenstvovanie students of technical institute of higher
Keywords: тренінг соціально-психологічний; підготовка професійна; фахівець; якість освіти; компетенція